2022
DOI: 10.3390/v14112436
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations to Decipher the Role of Phosphorylation of SARS-CoV-2 Nonstructural Proteins (nsps) in Viral Replication

Abstract: Protein phosphorylation is a post-translational modification that enables various cellular activities and plays essential roles in protein interactions. Phosphorylation is an important process for the replication of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). To shed more light on the effects of phosphorylation, we used an ensemble of neural networks to predict potential kinases that might phosphorylate SARS-CoV-2 nonstructural proteins (nsps) and molecular dynamics (MD) simulations to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These polyproteins are cleaved by M Pro and PL Pro to form 16 non-structural proteins (Nsp1-16) ( 105 ), Nsps are important for viral replication. Alomair et al ( 106 ) used neural networks and molecular dynamics simulation to predict the effect of phosphorylation on Nsps. Root mean square fluctuation values showed that phosphorylation has an impact on Nsp1-6 and Nsp16.…”
Section: Development Of Computational Biology For Sars-cov-2 Inhibito...mentioning
confidence: 99%
“…These polyproteins are cleaved by M Pro and PL Pro to form 16 non-structural proteins (Nsp1-16) ( 105 ), Nsps are important for viral replication. Alomair et al ( 106 ) used neural networks and molecular dynamics simulation to predict the effect of phosphorylation on Nsps. Root mean square fluctuation values showed that phosphorylation has an impact on Nsp1-6 and Nsp16.…”
Section: Development Of Computational Biology For Sars-cov-2 Inhibito...mentioning
confidence: 99%
“…Enforced physical distancing, hand hygiene, and arguably, proper usage of personal protective equipment, including wearing a surgical mask, remains the most effective way of controlling the spread of the disease. Most countries that have adopted such measures have reported some success in curbing the spread of the disease [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic coronavirus disease (COVID-19) is a serious malady caused by a new coronavirus known as severe acute respiratory syndrome (SARS-CoV-2). There is non-trustworthy remedy or vaccine accessible to fight versus SARS-CoV-2 [1][2][3][4][5][6] . More attempts to probe for antiviral agents against COVID-19 are essential, while phytochemicals can be powerful solution.…”
Section: Introductionmentioning
confidence: 99%